DENGUE OUTBREAK -IS THE PANIC JUSTIFIED ? - Shehzad, Sofia (Journal of Gandhara Medical and Dental Science, 2018)
In this era of startling developments in the medical field there remains a serious worry about the hazardous potential of various by products which if not properly addressed can lead to consequences of immense public concern. Hospitals and other health care facilities generate waste products which are evidently hazardous to all those exposed to its potentially harmful effects. Need for effective legislation ensuring its safe disposal is supposed to be an integral part of any country’s health related policy. This issue is of special importance in developing countries like Pakistan which in spite of framing various regulations for safeguarding public health, seem to overlook its actual implementation. The result unfortunately is the price wehave to pay not only in terms of rampant spread of crippling infections but a significant spending of health budget on combating epidemics which could easily have been avoided through effective waste disposal measures in the first place. Waste classified under the heading ’bio-hazardous’ includes any infectious or potentially infectious material which can be injurious or harmful to humans and other living organisms. Amongst the many potential sources are the hospitals or other health delivery centres which are ironically supposed to be the centres of infection control and treatment. Whilst working in these setups, health care workers such as doctors, nurses, paramedical staff and sanitation workers are actually the ones most exposed and vulnerable to these challenges. Biomedical waste may broadly be classified into Infectious and toxic waste. Infectious waste includes sharps, blood, body fluids and tissues etcwhile substances such as radioactive material and by-products of certain drugs qualify as toxic waste. Furthermore health institutions also have to cater for general municipal waste such as carton boxes, paper and plastics. The World Health Organisation has its own general classification of hospital waste divided into almost eight categories of which almost 15% (10% infectious and 5% toxic) is estimated to be of a hazardous nature while the remaining 85% is general non hazardous content.1A recent study from Faisalabad, Pakistan has estimated hospital waste generation around 1 to 1.5 kg / bed /day for public sector hospitals in the region,2while figures quoted from neighbouring India are approximately 0.5 to 2 KG / hospital bed /day.3 Elsewhere in the world variable daily hospital waste production has been observed ranging from as low as 0.14 to 0.49 kg /day in Korea4 and 0.26 to 0.89 kg/day in Greece5to as high as 2.1 to 3.83 kg/day in Turkey6 and 0.84 to 5.8 kg/day in Tanzania.7Ill effects of improper management of hospital waste can manifest as nosocomial infections or occupational hazards such as needle stick injuries. Pathogens or spores can be borne either through the oro-faecal or respiratory routes in addition to direct inoculation through contact with infected needles or sharps. Environmental pollution can result from improper burning of toxic material leading to emission of dioxins, particulate matter or furans into the air. The habitat can also be affected by illegal dumping and landfills or washing up of medical waste released into the sea or river. Potential organisms implicated in diseases secondary to mismanagement of hospital waste disposal include salmonella, cholera, shigella, helminths, strep pneumonia, measles, tuberculosis, herpesvirus, anthrax, meningitis, HIV, hepatitis and candida etc. These infections can cause a considerable strain on the overall health and finances of the community or individuals affected. The basic principal of Public health management i.e ’prevention is better than cure’ cannot be more stressed in this scenario as compared to any other health challenge. Health facilities must have a clear policy on hazardous waste management. To ensure a safe environment hospitals need to adopt and implement international and local systems of waste disposal. Hospital waste management plan entails policy and procedures addressing waste generation, accumulation, handling, transportation, storage, treatment and disposal. Waste needs to be collected in marked containers usually colour coded and leak proof. Segregation at source is of vital importance. The standard practice in many countries is the Basic Three Bin System ie to segregate the waste into RED bags/ boxes for sharps, YELLOW bags for biological waste and BLUE or BLACK ones for general/ municipal waste. All hospital staff needs to be trained in the concept of putting the right waste in relevant containers/ bags. They need to know that more than anything else this practice is vital for their own safety. The message can be reinforced through appropriate labelling on the bins and having posters with simple delineations to avoid mixing of different waste types. Sharps essentially should be kept in rigid, leak and puncture-resistant containers which are tightly lidded and labelled. Regular training sessions for nurses and cleaning staff can be organised as they are the personnel who are more likely to deal with waste disposition at the level of their respective departments. Next of course is transportation of waste products to the storage or disposal. Sanitary staff and janitors must be aware of the basic concepts of waste handling and should wear protective clothing, masks and gloves etc, besides ensuring regular practice of disinfection and sterilization techniques.8Special trolleys or vehicles exclusively designed and reserved for biomedical waste and operated by trained individuals should be used for transportation to the dumping or treatment site. Biomedical waste treatment whether on site or off site is a specialised entity involving use of chemicals and equipment intended for curtailing the hazardous potential of the material at hand. Thermal treatment via incinerators, not only results in combustion of organic substances but the final product in the form of non-toxicash is only 10 to 15% of the original solid mass of waste material fed to the machine. Dedicated autoclaves and microwaves can also be used for the purpose of disinfection. Chemicals such as bleach, sodium hydroxides, chlorine dioxide and sodiumhypochlorite are also effective disinfectants having specialised indications. Countries around the world have their own regulations for waste management. United Kingdom practices strict observance of Environmental protection act 1990, Waste managementlicensing regulations 1994 and Hazardous waste regulations 2005 making it one of thesafest countries in terms of hazardous waste disposal. Similar regulations specific for each state have been adopted in United States following passage of the Medical Waste tracking act 1988. In Pakistan, every hospital must comply with the Waste Management Rules 2005 (Environment Protection Act 1997), though actual compliance is far from satisfactory. It is high time that the government and responsible community organisations shape up to seriously tackle the issue of bio hazardous waste management through enforcement of effective policies and standard operating procedures for safeguarding the health and lives of the public in general and health workers in particular. Outbreaks, defined as excess cases of a particular disease or illness which outweighs the response capabilities, have the capacity to overwhelm health care facilities and need timely response and attention to details in order to avoid potentially disastrous sequelae . In this day and age when improvement in public health practices have significantly curtailed outbreak of various diseases, certain viral illnesses continue to make headlines. One of the notable vector borne infectious disease affecting significant portions of south east Asia in the early part of twenty first century is ’Dengue fever’. Dreaded as it is by those suffering from the illness, a lot of the hysteria created is secondary to a lack of education and understanding of the nature of the disease and at times a result of disinformation campaign for vested interests by certain political and media sections.’Dengue’ in fact is a Spanish word, assumed to have originated from the Swahili phrase -ka dinga peppo -which describes the disease as being caused by evil spirit. 1 Over the course of time it has been called ’breakbone fever’, ’bilious vomiting fever’, ’break heart fever’, ’dandy fever’, ’la dengue’ and ’Phillipine, Thai and Singapore hemorrhagic fever’ Whilst the first reported case referring to dengue fever as a water poison spread by flying insects, exists in the Chinese medical encyclopedia from Jin Dynasty (265-420 AD), the disease is believed to have disseminated from Africa with the spread of the primary vector, aedes egypti, in the 15th to 19th century as a result of globalisation of slave trade 45In 80% of the patients affected by this condition the presentation is rather insidious and at best characterized by mild fever. The classical ’Dengue fever’ present in about 5% of the cases is characterized by high temperature, body aches, vomiting and at times a skin rash. The disease may regresses in two to seven days. However inrare instances (<5%) it may develop into more serious conditions such as Dengue hemorrhagic fever whereby the platelet count is significantly reduced leading to bleeding tendencies and may even culminate in a more life threatening presentation i.e Dengue shock syndrome.6To understand the actual dynamics of Dengue epidemic it is important to understand the mode of its spread in affected areas. Aedes mosquito (significantly Aedes Egypti) acts a vector for this disease. Early morning and evening times7 are favoured by these mosquitos to feed on their prey. There is some evidence that the disease may be transmitted via blood products and organ donation. 8 Moreover vertical transmission (mother to child) has also been reported 9Diagnostic investigations include blood antigen detection through NS-I or nucleic acid detection via PCR. IO Cell cultures and specific serology may also be used for confirming the underlying disease. Whilst sporadic and endemic cases are part of routine medical practice and may not raise any alarm bells, outbreaks certainly need mobilization of appropriate resources for effective control. Needless to say ’prevention is better than cure’ and should be the primary target of the health authorities in devising strategies for disease control.The WHO recommended ’Integrated Vector control programme’, lays stress on social mobilisation and strengthening of public health bodies, coherent response of health and related departments and effective capacity building of relevant personnel and organisations as well as the community at risk. For Aedes Egypti the primary control revolves around eliminating its habitats such as open sources of water. In a local perspective in our city Peshawar, venue of the recent dengue epidemic, it may be seen in the form of incidental reservoirs such as receptacles and tyres dumped in open areas such as roof tops with rain water accumulating in them and provtdjng excellent breeding habitats, Larvicidal and insecticides may be added to more permanent sources such as watertanks and farm lands. There is not much of a role for spraying with organophosphorous agents which is at times resorted to for public consumption. Public education is the key to any effective strategy which must highlight the need for wearing clothing that fully covers the skin, avoiding unnecessary early morning and evening exposure to vector agents, application of insect repellents and use of mosquito nets. It is also important not to panic if affliction with the disease is suspected as in a vast majority of instances it is a self limiting illness without any long term harmful effects and needs simple conservative management like antipyretics and analgesics.An important consideration for responsible authorities in a dengue epidemic is to ensure that maximum management facilities for simple cases are provided at the community level through primary and secondary health care facilities and that the tertiary care hospitals are not inundated with all sort of patients demanding consultation. These later facilities should be reserved for those patients who end up with any complications or more severe manifestation of the disease.Research is underway to develop an ideal vaccine for Dengue fever. In 2016, a vaccine by the name ’Dengvaxia’ was marketed in Phillipines and Indonesia. However with development of new serotypes of the virus, its efficacy has been somewhat compromised.As for treatment , there are no specific antiviral drugs. Management is symptomatic revolving mainly around oral and intravenous hydration. Paracetamol (Acetaminophen) is used for fever as compared to NSAIDS such as Ibuprophen infusion as well as blood and platelet transfusion.Data to date shows that slightly more than twenty three thousand people have been diagnosed with dengue over the past three months ie August to October there is a lower risk of bleeding with the former. Those with more severe form of the disease may need Dextran 2017, in Peshawar, Pakistan with around fourteen thousand needing admission and about sixty nine recorded deaths. The mortality is well within the acceptable international standards of less than 1% for the disease. In the backdrop of all the debate surrounding the current epidemic, one can infer that such outbreaks are best addressed with effective planningwell ahead of the time before the disease threatens to spiral out of control. Simple measures such as covering water storage facilities, using larvicidals where practical, use of insect repellents, mosquito nets and avoiding unnecessary exposure can offerthe best protection. Public health messages via print and electronic media can help educate people in affected areas and allay any anxiety building up from a fear of developing life threatening complications. Health department must mobilise all its resources to ensure local management of diagnosed patients with simple dengue fever and facilitate hospital admission only for those suffering from more severe form of the disease. Moreover the media hype into such situations needs to be addressed through constant updates and discouraging any negative politicking on the issue. To sum up Dengue fever is not really an affliction to be dreaded provided it is viewed and managed in the right perspective.